Pengaruh Model Problem Based Learning Dalam Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas IV pada Mata Pelajaran Bahasa Indonesia - Sanah, Ines Faizatus; Taufik, Taufik; Karismawan, Muhammad Dani; Adi, Nur Romdlon Maslahul (Paedagogie, 2025)
As an effort to create an active, fun, and productive learning atmosphere so that students can be equipped with strong critical thinking skills that are ready to be applied in everyday life, this research was conducted in class IV of Al-Chusnaini Islamic Elementary School Sidoarjo involving 28 students as subjects. The research process took place in two cycles, each of which consisted of planning, implementation, observation, and reflection stages. Data were collected through quantitative analysis using observation, tests, and documentation. The tests given measured problem solving skills in Indonesian language subjects, while observations were made to monitor the learning process. The independent variable in this study is the Problem Based Learning model, while the dependent variable is students' critical thinking skills. The results showed a significant increase, with the average value of students' critical thinking skills increasing from 74.32 in the first cycle to 94.75 in the second cycle. Based on these findings, it can be concluded that the application of the Problem Based Learning model is effective in improving students' critical thinking skills on the material of fact and opinion sentences in class IV of Al-Chusnaini Islamic Elementary School Sidoarjo.